2018
DOI: 10.4236/tel.2018.86081
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Benefits of ERP Systems across the Different Manufacturing Industries of SMEs

Abstract: As a result of the ongoing economic crisis and the international market competition, Greek SMEs, particularly the ones focusing in manufacture and production, need to stay profitable by increasing efficiency, while reducing operational costs. Information collected, stored and processed by ERP systems help SMEs to reduce uncertainty, and improve operations and managerial decision-making. Manufacture SMEs could benefit from the implementation of an ERP system, as there are many aspects in the business to conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
2
0
5
Order By: Relevance
“…In the UK context, Ammar (2017), it was noticed that variations in management accounting practices that are due to ERP mobilisation have been used to address different managerial functions, including planning and decision‐making, across multiple cases operating in the UK context. Similarly, Goumas et al (2018) reported that ERP demonstrated various implications, both within and across different manufacturing categories, both for reducing uncertainty and for improving operations and managerial decision‐making.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 97%
“…In the UK context, Ammar (2017), it was noticed that variations in management accounting practices that are due to ERP mobilisation have been used to address different managerial functions, including planning and decision‐making, across multiple cases operating in the UK context. Similarly, Goumas et al (2018) reported that ERP demonstrated various implications, both within and across different manufacturing categories, both for reducing uncertainty and for improving operations and managerial decision‐making.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 97%
“…Neke financijske institucije koriste se određenim ERP modulima u uskim funkcionalnim područjima kao što su ljudski resursi i financijsko računovodstvo (Zhu, Kraemer & Dedrick, 2004). Ključno je pitanje u djelatnosti osiguranja upravo analiza podataka, a društva za osiguranje i reosiguranje u velikoj se mjeri oslanjaju na pohranu, obradu i upotrebu informacija pa se stoga i smatraju informacijski intenzivnim organizacijama (Glowalla & Sunyaev, 2013). Može se zaključiti kako su inovacije, implementacija i primjena novih tehnologija ključni pokretači promjena u financijskom sektoru (Ostagar, 2018).…”
Section: Uvodunclassified
“…Budući da se svi podaci koji se prikupljaju iz internog i eksternog okruženja društva pohranjuju u centraliziranu bazu podataka koja omogućava korisnicima izravan i jednostavan pristup bilo kojem podatku, može se očekivati da će implementacija IIS-a značajno utjecati na prikupljanje podataka koji se koriste u svrhu internog izvještavanja menadžera (Rom & Rohde, 2006;Granlund, 2011). U skladu s time, prethodna istraživanja potvrdila su da se podaci prikupljaju i obrađuju jednostavnije i ažurnije s pomoću IIS-a (Kanellou & Spathis, 2013;Etemadi & Kazeminia, 2014;Goumas, Charamis & Tabouratzi, 2018;Ostagar, 2018). Budući da suvremeno poslovno okruženje nameće potrebu za širim opsegom prikupljenih podataka, očekivano je da se u značajnoj mjeri računovodstveni, ali i nefinancijski podaci o poslovanju i iz poslovnog okruženja pohranjuju u IIS.…”
Section: Pregled Prethodnih Istraživanjaunclassified
See 2 more Smart Citations